Violencia de género y la salud afectiva en los estudiantes de la Escuela de Educación Básica Silvio Vidal Triviño - Manzaba Parraga, Fanny Marlene (2019)
Violence as such is a social problem that is increasingly increasing where it makes its exclusive appearance at home or outside it. We can also visualize it through the different technological means that allow us to know the multiple cases that happen in our country. As a result of this is reflected in the affectivity of the victim of this fact. The objective of this research project is to develop or implement in the elementary school "Silvio Vidal Triviño" a psychoeducational workshop on gender violence to improve the emotional health of its students, and in the same way to train parents and teachers belong to the aforementioned institution. For the determined elaboration of this project, we chose the development of a questionnaire of questions which helped to carry out the surveys corresponding to the educational community in general (students, parents and teachers). Through the surveys carried out, results were obtained which were reflected by the statistical graphs that helped in one way or another also to the total verification of the investigative problem. As a conclusion, it can be obtained that the application of the program results in the importance that the community in general needs to orient victims of gender violence as a prevention to this fact.